Origin of abnormal structural transformation in a (BiPb)FeO3/SrRuO3/SrTiO3 hetero-structure probed by Rutherford backscattering - Murtaza Bohra (Nature Portfolio, 2017)
Abstract Scientific efforts are growing to understand artificial BiFeO3/SrRuO3/SrTiO3-heterostructures, wherein an altered environment at each interface, caused by epitaxial strains, broken symmetry, off-stoichiometry and charge transfer, can generate a rich spectrum of exotic properties. Herein, (BiPb)FeO3/SrRuO3/SrTiO3-heterostructures were sputtered with various top (BiPb)FeO3-layers at different growth temperatures (T g). Strain relaxation at each interface changes with T g and generates an additional peak alongside with (BiPb)FeO3 at a high T g of 700 °C. Rutherford backscattering (RBS) was employed to understand this unusual behavior as to whether it is a mixture of two phases, layer splitting or inter-diffusion of elements. Surprisingly, complete overlapping of random and aligned RBS spectra from the sample with T g  = 700 °C indicates the presence of a large amount of defects/distortions at the interfaces. The RBS compositional analysis gives clear evidence of Fe and Ru vacancies to an extent that the structural integrity may not be maintained. This abnormal condition can be explained by the inter-diffusion of Pb and Bi elements into whole films and even into the top layer of the SrTiO3 substrate, which compensates for these vacancies by substitutional replacement and is responsible for the generation of the additional SrTi(BiPb)O3—peak. Below T c SrRuO 3, the magnetic properties change significantly with T g .